D-Serine Regulation of the Timing and Architecture of the Inspiratory Burst in Neonatal Mice - Eugenin-Leon, J; Chacon-Pacheco, M; Beltran-Castillo, S; Olivares-Arce, M; Ochoa-Sarmiento, M (Elsevier B.V., 2020)
D-serine, released from mouse medullary astrocytes in response to increased CO2 levels, boosts the respiratory frequency to adapt breathing to physiological demands. We analyzed in mouse neonates, the influence of D-serine upon inspiratory/expiratory durations and the architecture of the inspiratory burst, assessed by pwelch s power spectrum density (PSD) and continuous wavelet transform (CWT) analyses. Suction electrode recordings were performed in slices from the ventral respiratory column (VRC), site of generation of the respiratory rhythm, and in brainstem-spinal cord (en bloc) preparations, from the C5 ventral roots, containing phrenic fibers that in vivo innervate and drive the diaphragm, the main inspiratory muscle. In en bloc and slice preparations, D-serine (100 μM) reduced the expiratory, but not the inspiratory duration, and increased the frequency and the regularity of the respiratory rhythm. In en bloc preparations, D-serine (100 μM) also increased slightly the amplitude of the integrated inspiratory burst and the area under the curve of the integrated inspiratory burst, suggesting a change in the recruitment or the firing pattern of neurons within the burst. Time-frequency analyses revealed that D-serine changed the burst architecture of phrenic roots, widening their frequency spectrum and shifting the position of the core of firing frequencies towards the onset of the inspiratory burst. At the VRC, no clear D-serine induced changes in the frequency-time domain could be established. Our results show that D-serine not only regulates the timing of the respiratory cycle, but also the recruitment strategy of phrenic motoneurons within the inspiratory burst. © 2020 Elsevier B.V.